THE INFLUENCE OF TECHNOLOGY READINESS AND LEARNING MOTIVATION ON STUDENTS’ PERFORMANCE IN ONLINE LEARNING DURING THE COVID 19 PANDEMIC: A STORY OF INDONESIAN HIGHER EDUCATION STUDENTS - Budi Tiara Novitasari; Mimin Nur Aisyah; Ponty S.P. Hutama; Sukirno Sukirno (Jurnal Ilmiah Global Education, 2023)
Covid 19 Pandemic has changed the learning process at various levels. Higher education has been changing how it operates in meeting the needs of teaching and learning in the midst of restrictions due to the Covid 19 outbreak. Online learning has become the best option to ensure that the learning process continues while the outbreak remains controlled. Regardless of its flexibility, it is undeniable that many parties in the education system doubt the effectiveness of online learning in assisting students in achieving their learning objectives. This research aimed to scrutinize factors affecting students’ learning effectiveness in online learning. Using online questionnaires distributed to university students across Indonesia, this research found that technology readiness positively influencing learning motivation and students’ performance, and later learning motivation positively influences students’ performance.